New Aspects of Foreign and Internal Policy of Mariano Raho People’s Party in Spain - N. E. Anikeeva (Vestnik MGIMO-Universiteta)
The conservative People’s party led by M. Raho won in the general еlections in Spain in november 20, 2011. The spanish socialists went into opposition. There began a new stage in the political history of the country.